Alam sebagai Baileo Kehidupan: Suatu Kajian Teologi - Vilma Vielda Ayhuan; Nancy Novitra Souisa; Monike Hukubun (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2021)
The aim of this article is to explore theologically the meaning of Baileo at Negri Soya as a contribution to protecting nature from environmental damages which are serious problems that have attracted global concern. By conducting interviews, and then searching the meaning of Baileo, the researcher found out that giving meaning to nature as baileo shaped how people in Negri Soya see and protect nature. They understood nature not as an object to be exploited, but as an integral part of human beings’ existence that must be protected. Nature as a living baileo is God’s sacral creation. In addition, the utilization of natural elements in all ritual processions in baileo does not reflect a hierarchical concept. There is no separation among God, ancestors, human beings, and nature. Nature is not only be perceived as a source for learning and experiencing God's great creation but also as a subject to praise God.